THE INFLUENCE OF MACROECONOMIC VARIABLES ON THE RUPIAH EXCHANGE RATE FOR THE UNITED STATES DOLLAR - Ni Putu Yuni Sundari; I Made Endra Kartika Yudha (Adisam Publisher, 2025)
The exchange rate serves as a crucial economic indicator due to its broad impact on various facets of a nation's economy. This study aims to investigate the impact of key macroeconomic variables on the Indonesian rupiah's exchange rate vis-à-vis the US dollar. Specifically, it examines inflation, Bank Indonesia's interest rates, and the Federal Reserve's interest rates using secondary data from official sources spanning from 1990 to 2022. Employing a quantitative approach with associative modeling, the study utilizes the Autoregressive Distributed Lag (ARDL) analysis technique for data analysis. The results indicate that inflation, Bank Indonesia's interest rates, and the Fed's interest rates collectively influence the rupiah's exchange rate against the US dollar. These variables demonstrate short-term impacts on the exchange rate, with persistent effects observed in the long term, emphasizing their role in maintaining exchange rate stability. This research underscores the importance of continuously monitoring and evaluating these macroeconomic factors to ensure stability in the rupiah's exchange rate against the US dollar.